How gender and boat-side affect shape characteristics of force-angle profiles in single sculling: Insights from functional data analysis - Warmenhoven, J.; Cobley, S.; Draper, C.; Harrison, A.; Bargary, N.; Smith, R. (Journal of Science and Medicine in Sport, 2018)
Objectives: To examine whether gender or side of the boat influenced shape characteristics of the force-angle profile in on-water single sculling. Design: Cross-sectional study design. Methods: Bivariate functional principal components analysis (bfPCA) was applied to force-angle data to identify the main modes of variance in curves of forty highly skilled male and female rowers (national and international level), rowing at 32 strokes per minute in a single scull boat. Results: Separate discriminant function analyses for each side of the boat showed strong classification of rowers for gender. Force application close to (or closely around) the perpendicular oar position was demonstrated to be different between genders. A mixed ANOVA exploring gender, boat side and their interaction revealed that bow and stroke side forces were also statistically different from each other independently of gender. A main effect, independent of side of the boat, was also present for gender and no interaction was found between gender and boat side. Bow side forces seemingly acted as a driver of power and peak force production, while stroke side forces may have acted as a mediator of propulsive forces with an additional potential role in steering due to known asymmetrical offsets in boat rigging. Conclusions: Results demonstrate that propulsive force differences according to gender and boat-side are evident and must be acknowledged and accounted for before force-angle graphs are explored relative to performance measures.